School Resource and Performance Inequality : Evidence from the Philippines - Yamauchi, Futoshi; Parandekar, Suhas (World Bank, Washington, DC, 2014)
This paper examines inequality patterns of school and teacher resources as well as student performance in the Philippines. School and teacher resources, measured by pupil classroom and teacher ratios and per-pupil teacher salary, became more unequal over time. Strikingly, a large portion of the variation is attributed to their within-division distributions, especially the non-city areas in each province (rural schools), where pupil classroom and teacher ratios have significantly positive returns in terms of student test scores. Concavity built into the education production function implies that reallocation of teachers and classrooms within a division can potentially increase average test scores. The estimates also imply that it is optimal to deploy young, inexperienced teachers to rural schools and reassign them to urban schools when the teachers are more experienced.